The Effect of Work-life Quality and Transglobal Leadership on Employee Performance of Sharia Saving-load and Finance Cooperative - Zam Zam Saepul Mubarok; Andang Heryahya; Indra; Rusdi Hamka Lubis (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2022)
This study aims to examine the effect of work-life quality and transglobal leadership on employee performance of Sharia Saving-Loan and Finance Cooperative. The population of this study consisted of employees of sharia saving-loan and finance cooperative in Banten. Sampling was carried out using the minimum criteria from the SEM-PLS, ranging from 35 to 100. Data was obtained by using a questionnaire. This research is a quantitative study. The data were analyzed using Structural Equation Modelling (SEM) and processed using Partial Least Square (PLS) analysis with the Smartpls 3.0 application. This study found that the work-life quality has a positive and significant effect on organizational commitment, the work-life quality has a positive and significant effect on employee performance, transglobal leadership has a positive and significant effect on organizational commitment, transglobal leadership does not have any effect on employee performance, organizational commitment has a positive effect and significant on employee performance, organizational commitment mediates the effect of work-life quality on employee performance and organizational commitment mediates the effect of transglobal leadership on employee performance.